The Students Perceptions About School Climate in Public Vocational High Schools IV Jurai District Painan - Yuda, Yuda Maimandre; Syahril; Lusi Susanti; Tia Ayu Ningrum (Journal of Practice Learning and Educational Development, 2023)
A conducive school climate is very important because this will support the teaching and learning process in accordance with expectations and will benefit all parties. Increasing teacher enthusiasm in teaching and learning enthusiasm of students is an important hope in achieving a good and conducive climate. School climate is an atmosphere that plays an active role in supporting the creation of a good school environment, which will affect student learning outcomes and achievements. This study aims to look at the climate of schools in the IV Jurai sub-district in terms of the dimensions of relationships, system changes and improvements, the physical environment and personal development. The research method used is descriptive research. The population in this study is SMKN in IV Jurai Painan district. The results of research on aspects of the relationship dimension with an average score of 4.11 with a conducive category, dimensions of change and improvement of the system with an average score of 3.70 with a conducive category, dimensions of the physical environment with an average score of 4.02 conducive category and dimensions of personal development with an average score of 3.73 in the conducive category.